2001
DOI: 10.1182/blood.v97.5.1511
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of rearranged immunoglobulin heavy chain variable region genes in peripheral blood B cells of preterm infants is restricted by short third complementarity-determining regions but not by limited gene segment usage

Abstract: The immunoglobulin diversity is restricted in fetal liver B cells. This study examined whether peripheral blood B cells of extremely preterm infants show similar restrictions (overrepresentation of some gene segments, short third complementarity-determining regions [CDR3]). DNA of rearranged immunoglobulin heavy chain genes was amplified by polymerase chain reaction, cloned, and sequenced. A total of 417 sequences were analyzed from 6 preterm infants (25-28 weeks of gestation), 6 term infants, and 6 adults. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 14 publications
(7 reference statements)
6
43
1
Order By: Relevance
“…These observations suggest that the lymphocyte population in these chimeric mice is in a dynamic state, with cells being selected at certain points. 3) HCDR3 lengths as well as the presence of N nucleotides are similar to those described for human cord blood and term infants (40,42,43). This shows that the TdT expressed by lymphocyte precursors was functional in the murine environment.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…These observations suggest that the lymphocyte population in these chimeric mice is in a dynamic state, with cells being selected at certain points. 3) HCDR3 lengths as well as the presence of N nucleotides are similar to those described for human cord blood and term infants (40,42,43). This shows that the TdT expressed by lymphocyte precursors was functional in the murine environment.…”
Section: Discussionsupporting
confidence: 63%
“…The J H 4 segment is most commonly used by normal fetal (40) and cord blood B cells (41), as was the case for 58% of the lymphocytes analyzed from transplanted mice. The average of the mean HCDR3 lengths for the population was 15.2 Ϯ 0.7 codons and falls within limits previously described for cord blood and term infants (42,43). Each junction represented a unique sequence and there was clear evidence for N nucleotide insertion, i.e., TdT activity.…”
Section: Ig V H Gene Utilization In Chimeric Micementioning
confidence: 71%
“…With increasing fetal maturity, the importance of proximity decreases but still plays a role in neonates at term who favor the D H 6, D H 7 families and J H 3, J H 4, whereas in adults D H 2, D H 3 families and J H 6 are preferably used (9,21). We found that Ag exposure did not accelerate these developmental trends in the repertoire.…”
Section: Restrictions In the Neonatal V H D H And J H Gene Segmenmentioning
confidence: 62%
“…In neonates, V H gene segments from across the entire locus were used in a frequency pattern similar to the one seen in adults, suggesting that proximity of the V H gene segment to the D H locus seems to play a much more limited role in rearrangement bias in humans than in mice (9,18,19). Furthermore, the IgG and the IgM repertoire showed a similar V H gene segment usage.…”
Section: Restrictions In the Neonatal V H D H And J H Gene Segmenmentioning
confidence: 86%
See 1 more Smart Citation